Diagnosing Herbicide Injury in Peanut - S. Morichetti; Jason Ferrell (EDIS, 2010)
SS-AGR-327, a 12-page illustrated fact sheet by S. Morichetti and J. Ferrell, details mechanism of action, behavior in plants, and symptomology for various types of herbicides used in peanut production. Published by the UF Department of Agronomy, December 2009.